Availability of the pharmaceutical service as a public health protection correlate − the legal approach - Jachowicz, Michał; Kobylarz, Michał; Skowron, Agnieszka (Dostępność usługi farmaceutycznej jako korelat ochrony zdrowia publicznego – ujęcie prawne, 2020)
The functioning of the pharmacy market in Poland is subject to strict statutory regulation. In striving to ensure the widest availability of services provided by generally accessible pharmacies to patients, the legislator introduced a solution consisting in granting county (‘powiat’) councils the power to issue local acts of law regarding the establishment of working hours of generally accessible pharmacies locally. Compliance with this obligation, however, faces various difficulties on the part of both pharmacies and self-government bodies, which negatively affects the effectiveness of the existing solution. The subject of this article is the assessment of existing legal solutions in the discussed area, together with a review of the proposed statutory changes developed by pharmacies self-government and the Association of Polish Counties (‘powiat’)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 2, s. 56-71
Keywords: generally accessible pharmacy; pharmacist; pharmaceutical law; public health; apteka ogólnodostępna; farmaceuta; prawo farmaceutyczne; zdrowie publiczne